WR galaxies and PAH: observations and modeling - Yeghikyan, A.; Martirosyan, J.
This report analyzes the archival data of the Spitzer observatory for 9 WR galaxies showing PAH emission lines at 6.2 and 7.7 μ. For these galaxies, the e ective radii of the emitting regions and the total number of hydrogen ionizing quanta were calculated on the base of the uxes corrected for interstellar extinction. Using the observed values (which are obtained using SDSS data), and taking as an example stars of the WNh type (Ts = 50000 K, R = 20 Ro), the number of massive WR stars in the cluster and the distance to the nearest neighbor are determined. With these data, the theoretical Cloudy models, in particular, the distribution of H and He, C, O, Ne atoms and ions along the radius are calculated. The theoretical intensities of the characteristic PAH bands at 6.2 and 7.7 μ were obtained for two types of PAH (containing 15 and 120 carbon atoms, respectively). The corpuscular radiation doses accumulated in PAH molecules due to hard irradiation by MeV protons were calculated and it was shown that such molecules had to decay for a time less than the lifetime of the cluster. A conclusion is drawn about the permanent source of PAH, most likely, the remnants of supernova explosions.
Keywords: Astronomy